Gun violence in United States during the second year of the COVID-19 pandemic - Ssentongo, Paddy; Ssentongo, Anna; Heilbrunn, Emily S.; Chinchilli, Vernon M. (Frontiers in Public Health, 2023)
Objective In the first year of the COVID-19 pandemic, gun violence (GV) rates in the US rose by 30%. We estimate the relative risk of GV in the US in the second year compared to the first year of the pandemic, both in time and space. Methods Daily police reports of gun-related injuries and deaths in the 50 states and the District of Columbia from March 1st, 2020, to February 28, 2022, were obtained from the GV Archive. Generalized linear mixed-effects models in the form of Poisson regression analysis were utilized to estimate the state-specific rates of GV. Results Nationally, GV rates during the second year of the pandemic (March 1, 2021, through February 28, 2022) remained the same as that of the first year March 1, 2020, through February 28, 2021) [Intensity Ratio=0.996; 95% CI 0.98, 1.01; p=0.5]. Nevertheless, hotspots of GV were identified. Nine (18%) States registered a significantly higher risk of GV during the second year of the pandemic compared to the same period in the first year. In 10 (20%) States, the risk of GV during the second year of the pandemic was significantly lower compared to the same period in the first year. Conclusion GV risk in the US is heterogeneous. It continues to be a public health crisis, with 18% of the states demonstrating significantly higher GV rates during the second year of the COVID-19 pandemic compared to the same timeframe one year prior.